Stress at work place and its impact on employee performance - Lakshmi Narahari, Ch; Koneru, Kalpana (International Journal of Engineering and Technology, 2018)
The emphasis on management of Stress at work place (WS) in the corporate world assumes that the ability to manage Stress at work place is associated with enhanced employee performance which suggests that WS is a vital tool having sturdy and significant impact on both em-ployeeâ€™s employee performance and overall employee performance. Performance is important as it determines the survival of the organiza-tion and it also reflects how the organization can cope in todayâ€™s challenging business environment. The current paper is an attempt to brief the work done in the field of WS and employee performance by discussing various studies conducted around the world. The current paper has compiled the works done on the connection between Stress at work place and workplace performance and based on synthesis of the past studies has created a model that depicts the relationship between the various variables that contribute to Stress at work place and its impact on employee performance.Â